Effect of Temperature on Concrete Carbonation Performance - Peng Liu; Ying Chen; Zhiwu Yu; Rongling Zhang (Advances in Materials Science and Engineering, 2019)
In this study, the effect of temperature on macroperformance and microcharacteristic of carbonized concrete was investigated. The carbonation depth, compressive strength, and surface strain of concrete under different simulated environments for 28 d were measured. XRD and ESEM-EDS analysis were conducted to present the phase composition, types of hydration products, and microstructure characteristics of samples before and after carbonation. The results showed that the effects of temperature on carbonation depth, strain, and compressive strength were significant. There was a linear relation between temperature and carbonation depth as well as compressive strength of concrete. The effects of environment factors on concrete surface strain after carbonation manifested as the strain value and the slope of linear segment of strain curve. Significant differences of phase composition and hydration products were observed before and after the carbonation, which mainly manifested as attenuation and disappearance of diffraction peaks of hydration products. Temperature affects the crystal form of the carbonation products.